Incidence and survival patterns of cranial chordoma in the United States. (29th October 2013) - Chambers, Kyle J.; Lin, Derrick T.; Meier, Josh; Remenschneider, Aaron; Herr, Marc; Gray, Stacey T.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine trends in survival patterns for cranial chordoma in the United States. Study Design A cross‐sectional analysis of a national healthcare database. Methods All cases of microscopically confirmed cranial chordoma between 1973 and 2009 from the Surveillance, Epidemiology, and End Results (SEER) program of the National Cancer Institute were examined. Age‐adjusted incidence and survival rates were calculated and stratified by treatment. Additionally, in order to assess trends over time, comparisons in survival were conducted for 3 calendar year cohorts: 1975 to 1984, 1985 to 1994, and 1995 to 2004. Results A total of 594 cases of microscopically confirmed chordoma involving cranial sites were identified, which accounted for 42% of all chordomas. Age‐adjusted incidence rate (IR) of all chordomas was 0.089 per 100, 000. Overall median survival time with surgery plus radiation was 9.2 years. Age and treatment modality were found to influence patient survival. Specifically, age > 50 years was associated with a significant increase in mortality rate (P < .05). Five‐year survival for the 1975 to 1984, 1985 to 1994, and 1995 to 2004 cohort was 48.5%, 73.0%, and 80.7%, respectively, with improved survival in the more recent cohorts (P < 0.01). Conclusion This study provides new data regarding survival patterns of cranial chordoma in the United States, with a trend toward improvement in survival in recent decades. Level of Evidence NA. Laryngoscope, 124:1097–1102, 2014